Development of Test Stand Prototype for Rail Vehicles Brake Components Testing - Juraj Gerlici; Tomas Lack; Jozef Harusinec (Communications - Scientific letters of the University of Zilina, 2014)
The paper deals with the new RAILBCOT test stand building reasons explanation. A project features definition is described. There is possible to perform the railway wheel tread profiles wear research under the rail vehicle in operation conditions simulation. This simulation is possible to execute on the test bench. An important feature of the research is the equivalent conicity change analysis. The paper outlines the stand operation principles a main structure components design and components parameters specification, the tests control, data acquisition and data assessment.